2005
DOI: 10.1175/jcli3457.1
|View full text |Cite
|
Sign up to set email alerts
|

Western North Pacific Tropical Cyclone Intensity and ENSO

Abstract: The influence of the El Niño-Southern Oscillation (ENSO) on tropical cyclone intensity in the western North Pacific basin is examined. Accumulated cyclone energy (ACE), constructed from the best-track dataset for the region for the period 1950-2002, and other related variables are analyzed. ACE is positively correlated with ENSO indices. This and other statistics of the interannually varying tropical cyclone distribution are used to show that there is a tendency in El Niño years toward tropical cyclones that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
481
3
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 630 publications
(539 citation statements)
references
References 33 publications
(34 reference statements)
51
481
3
4
Order By: Relevance
“…The top 10 disasters analyzed in the study provide some evidence of a possible influence of El Niño events to produce favorable conditions to induce disasters in the Pacific coast. During El Niño, the vertical wind shear weakens in the Eastern Pacific favoring intensification (e.g., Bell and Chelliah, 2006) and the TCs tend to be longer-lived and more intense (e.g., Camargo and Sobel, 2005). Looking at the large-scale conditions that characterized the top 25 TCs providing largest rainfall, we found that 10 of the TCs occurred during El Niño, 10 during neutral conditions, and only five during La Niña.…”
Section: The Enso Phasementioning
confidence: 79%
“…The top 10 disasters analyzed in the study provide some evidence of a possible influence of El Niño events to produce favorable conditions to induce disasters in the Pacific coast. During El Niño, the vertical wind shear weakens in the Eastern Pacific favoring intensification (e.g., Bell and Chelliah, 2006) and the TCs tend to be longer-lived and more intense (e.g., Camargo and Sobel, 2005). Looking at the large-scale conditions that characterized the top 25 TCs providing largest rainfall, we found that 10 of the TCs occurred during El Niño, 10 during neutral conditions, and only five during La Niña.…”
Section: The Enso Phasementioning
confidence: 79%
“…Intraseaonal variability was enhanced during the developing summer of El Niñ o year (Teng and Wang 2003). Typhoon activity and rainfall associated with typhoon increase during the developing summer of El Niñ o year (Camargo 2005;Kubota and Wang 2009). Due to the activated convection, southerly wind blows stronger toward the western North Pacific monsoon region.…”
Section: Possible Mechanisms For Interannual Variabilitymentioning
confidence: 98%
“…Zonal wind shear between equatorial and o¤-equatorial regions of the western North Pacific becomes larger. Tropical cyclones are more active and rainfall associated with typhoons increases over the western North Pacific region during the El Niñ o developing summer (Camargo 2005;Kubota and Wang 2009). When the Philippine Sea anticyclone is formed from autumn, convection is suppressed over the o¤-equatorial region (Wang and Zhang 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies by Klotzbach (2006) and Goldenberg et al (2001) suggest that changes in long-term Atlantic hurricane activity are more influenced by natural variability, such as the Atlantic Multidecadal Oscillation (AMO), than by anthropogenic changes. In addition to the internal variability of the AMO and the SST rise due to global warming, other climatic features that vary on faster time-scales, such as the North Atlantic Oscillation (NAO) (Elsner et al, 2000), the quasi-biennial oscillation (QBO) (Shapiro, 1982;Gray, 1984), the El Niño Southern Oscillation (ENSO) (Bove et al, 1998;Camargo and Sobel, 2005) and circulation changes over the Atlantic (Zehr, 1992;DeMaria et al, 1993; have also been shown to be related to hurricane activity.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, then, the underlying mean number of landfalls could be represented purely as a constant fraction of the total number of Atlantic hurricanes. However, if we delve deeper into the issue and look at individual storms it is clear that environmental factors influence where the Atlantic storms go and hence the steering of any particular storm towards land (Bove et al, 1998;Camargo and Sobel, 2005). What is less understood is whether these environmental factors should be treated as noise on interannual timescales or whether the probability of landfall varies in concert with the interannual basin activity such that there is no consistent relationship between the number of basin and landfalling storms.…”
Section: Introductionmentioning
confidence: 99%